2016
DOI: 10.1002/mds.26849
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia structure in Tourette's disorder and/or attention‐deficit/hyperactivity disorder

Abstract: We found no evidence that Tourette's disorder, attention-deficit/hyperactivity disorder severity, or a combination thereof are associated with structural variation of the basal ganglia in 8- to 12-year-old patients. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…One apparently robust result, described best in a relatively large prospective study by Peterson and colleagues (Peterson et al, 2003;Bloch et al, 2005), is decreased caudate nucleus volume. Recent, relatively large morphometry studies in Tourette syndrome and control children, however, did not identify changes in caudate or putamen volumes in Tourette syndrome subjects (Greene et al, 2017;Forde et al, 2017). Greene et al (2017) identified only volume changes in the thalamus, hypothalamus, and midbrain.…”
Section: Imaging Resultsmentioning
confidence: 90%
“…One apparently robust result, described best in a relatively large prospective study by Peterson and colleagues (Peterson et al, 2003;Bloch et al, 2005), is decreased caudate nucleus volume. Recent, relatively large morphometry studies in Tourette syndrome and control children, however, did not identify changes in caudate or putamen volumes in Tourette syndrome subjects (Greene et al, 2017;Forde et al, 2017). Greene et al (2017) identified only volume changes in the thalamus, hypothalamus, and midbrain.…”
Section: Imaging Resultsmentioning
confidence: 90%
“…The present functional magnetic resonance imaging (fMRI) study aimed to increase this understanding by investigating neural reward processing in children with TS and/or ADHD and healthy controls. Of this sample, basal ganglia structure, glutamate levels, and anterior cingulate cortex cytoarchitecture have been reported previously (Forde et al, 2018(Forde et al, , 2017Naaijen et al, 2017).…”
Section: Introductionmentioning
confidence: 76%
“…The shape of the neurodevelopmental trajectory may be different in patients compared to controls, and persistent cases may present with stronger abnormalities (Debes et al, 2015). Notably, structural abnormalities in basal ganglia are more apparent in older TS samples (Forde et al, 2017). Discrepancies could also be due to variations in paradigms used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo MRI studies of basal ganglia volume and shape in TS have produced differing results (reviewed in Greene et al (2017) ). A study of 47 children age 8-12 with TS, and controls with or without ADHD, found no significant group differences ( Forde et al , 2017 ).…”
Section: Resultsmentioning
confidence: 99%